Bi-rotor micro hydro power plant for energy supply to isolated consumers - D. Obozov, Alaybek; A. Akparaliyev, Ruslan; T. Mederov, Taalaybek; G. Krasnov, Victor (International Journal of Engineering and Technology, 2018)
This paper is dedicated to comparative analysis and description of a micro hydroelectric power plant with bi-rotor hydro generator. Based on the characteristics analysis, this paper describes a renewable energy source for a small watercourse; the feasibility of micro hydroelectric power plants with bi-rotor hydro generator is demonstrated. The features of their operation require in-depth research to substantiate parameters of such installations. This paper presents the analysis of the usage of micro hydroelectric solutions with bi-rotor hydro generator. The lattice theory problem was solved, which made it possible to determine the shape of the profile according to a given law of velocity distribution (pressure) on the contour. The experimental stand was developed, and the experiments were conducted to identify the dependence of the frequency of rotation from the flow and the dependence of the rotational frequencies of hydro turbines from various loads. Based on the results obtained, the optimum values of the rotational speed were identified. Presented results of experimental research are of significance and can be applied practically in design of micro hydroelectric power plants with bi-rotor hydro generator. Keywords: Bi-Rotor Hydro Generator; Differential Equation; Rotational Flows; Function; Hydraulic Models; Kinetic Energy; Renewable Energy Sources; Velocity Measurements.                                                                                                                     This paper is dedicated to comparative analysis and description of a micro hydroelectric power plant with bi-rotor hydro generator. Based on the characteristics analysis, this paper describes a renewable energy source for a small watercourse; the feasibility of micro hydroelectric power plants with bi-rotor hydro generator is demonstrated. The features of their operation require in-depth research to substantiate parameters of such installations. This paper presents the analysis of the usage of micro hydroelectric solutions with bi-rotor hydro generator. The lattice theory problem was solved, which made it possible to determine the shape of the profile according to a given law of velocity distribution (pressure) on the contour. The experimental stand was developed, and the experiments were conducted to identify the dependence of the frequency of rotation from the flow and the dependence of the rotational frequencies of hydro turbines from various loads. Based on the results obtained, the optimum values of the rotational speed were identified. Presented results of experimental research are of significance and can be applied practically in design of micro hydroelectric power plants with bi-rotor hydro generator.